“Earlyploid” - Tetraploid Annual Ryegrass - Ann R. Blount; Gordon M. Prine; Cheryl L. Mackowiak; Kevin E. Kenworthy; Jeffery C. Jones; Paul E. Reith (EDIS, 2011)
Earlyploid, developed at the UF/IFAS North Florida Research and Education Center, is a large-seeded, upright, early forage-producing and early maturing annual ryegrass. Regional variety trials show it is the earliest tetraploid ryegrass cultivar available commercially. It offers excellent disease resistance and sufficient cold tolerance to be grown successfully in the southern annual ryegrass region of the U.S. This 1-page fact sheet was written by A.R. Blount, G.M. Prine, C.L. Mackowiak, K.E. Kenworthy, J.C. Jones, and P.E. Reith, and published by the UF Department of Agronomy, October 2011.